Safe provision of nursing care as predicted by nursing students: A cross-sectional study - Andrea Solgajová; Dominika Kohanová; Dana Zrubcová; Ľuboslava Pavelová (Tehran University of Medical Sciences, 2024)
Background & Aim: Assessment of safety culture and nursing students' competencies in patient safety is essential for readiness to provide quality and safe care. The objectives of the study are to examine how nursing students perceive patient safety culture and to evaluate factors that may influence their perceptions. Methods & Materials: A descriptive cross-sectional study was conducted using the Slovak version of the Hospital Survey on Patient Safety Culture for Nursing Students and the Questionnaire for Measuring Demographic Variables and Information on the Education Process. The study involved 242 nursing students from two faculties in Slovakia. Data were analyzed using descriptive and inferential statistics. Results: None of the dimensions of patient safety culture was rated by the nursing students above the necessary level of 75 %. Statistically significant correlations and differences were found between the nursing students' perceptions of patient safety culture and some selected sociodemographic variables. Multiple regression analysis revealed significant associations between the nursing students' perceptions of patient safety culture and overall patient safety grade, the number of reported events in the workplace, and the number of reported events by nursing students. Conclusion: Recognising nursing students' perceptions of patient safety culture enables identification of weaknesses, and early implementation of targeted interventions and educational initiatives to increase overall patient safety in care provision. Future research should focus on recognizing relationships between perceived patient safety culture, teamwork, education, and indicators of safe and quality care during clinical training from nursing students' perspective.